Reliability Analysis of State Building in Banjar District - Sumantri, Rahmah; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
According to the Law of the Republic of Indonesia Number 28 of 2002, it is stated that every building must meet administrative requirements and technical requirements by the function of the building. In addition, according to the Regulation of the Minister of Public Works No. 25 of 2007, it is stated that the building before being used/used must obtain a Function-worthy Certificate (SLF). As of 2022, the condition of state buildings in Banjar Regency has not yet passed the issuance of the Certificate of Feasibility of Function (SLF). This is due to the limited capacity of the Regional Government in the utilization, preservation, and demolition of buildings due to the limited regional budget. The approach used in this research is the quantitative method. The research stage begins by analyzing the level of reliability of state buildings in Banjar Regency (reliable, less reliable, and unreliable) where the components of the assessment consist of architecture, structure, utilities and fire protection, accessibility, and building and environmental planning. Next, analysis state buildings in Banjar Regency which are important are handled first based on a priority scale using the Analytical Hierarchy Process (AHP) method from the results of filling out the questionnaire. The state building is used as a pilot project for the Regional Government so that appropriate recommendations for handling are formulated based on the results of the building reliability assessment. Based on the research, an analysis of the reliability level of the building has been successfully compiled, namely, for the DPRD Secretariat building of 78.34% (less reliable), the Development Planning, Research, and Regional Development Agency building of 78.38% (less reliable), Revenue Service Building Region by 77.61% (less reliable), Public Works Office Building, Spatial Planning and Land by 78.42% (less reliable), The Regional Financial and Asset Management Agency Building is 77.66% (less reliable), and the Health Service Building is 75.31% (less reliable). Based on the results of the analysis using the Analytical Hierarchy Process (AHP) method, it was found that state buildings are essential to be handled first based on a priority scale, namely the Health Office Building by 34%. To meet the reliability of buildings, the Health Office has made recommendations for maintenance, repair, restoration, overhaul/ demolition, and new replacement of building reliability components. Based on the results of the analysis using the Analytical Hierarchy Process (AHP) method, it was found that state buildings are essential to be handled first based on a priority scale, namely the Health Office Building by 34%. To meet the reliability of buildings, the Health Office has made recommendations for maintenance, repair, restoration, overhaul/ demolition, and new replacement of building reliability components. Based on the results of the analysis using the Analytical Hierarchy Process (AHP) method, it was found that state buildings are essential to be handled first based on a priority scale, namely the Health Office Building by 34%. To meet the reliability of buildings, the Health Office has made recommendations for maintenance, repair, restoration, overhaul/ demolition, and new replacement of building reliability components.